Ecological and public health aspects of stable flies (Diptera :muscidae): microbial interactions - Mramba, Furaha W. (Kansas State University, 2006)
Stable fly, Stomoxys calcitrans (L.), and house fly, Musca domestica L., are two major pests affecting both confined and pastured livestock in the United States. It costs livestock producers millions of dollars annually to reduce populations of these two pests. Control of stable flies and house flies based on chemical insecticides is only marginally effective and unsustainable in the long term due to the development of insecticide resistance. This has created a demand for alternative methods which are environmentally friendly and cost effective for the management of these pests. Information on stable fly and house fly oviposition behavior and the aggregation and segregation of their immatures may help in an integrated pest management control program for these pests. This research identified specific bacterial species from the surface of stable fly eggs which are suspected of releasing chemical cues used to induce gravid females to oviposit at sites where eggs have been deposited and inhibit additional deposition of eggs in the same habitat when it is already colonized. My research also showed that stable fly and house fly larvae tend to be aggregated in distribution, even in apparently homogenous habitats, and to be spatially segregated from each other. Finally, I evaluated the vector competence of stable flies for an emerging food-borne pathogen, Enterobacter sakazakii, showing that this fly species is potentially a good vector for this pathogen.
Keywords: stable fly; house fly; Biology, Entomology (0353)